2018
DOI: 10.1111/clr.13287
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of peri‐implantitis treatment and supportive care: A systematic review

Abstract: Objectives: To report the clinical outcomes for patients with implants treated for peri-implantitis who subsequently received supportive care (supportive peri-implant/ periodontal therapy) for at least 3 years. Material and methods:A systematic search of multiple electronic databases, grey literature and hand searching, without language restriction, to identify studies including ≥10 patients was constructed. Data and risk of bias were explored qualitatively. Estimated cumulative survival at the implant-and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(133 citation statements)
references
References 38 publications
4
113
0
16
Order By: Relevance
“…SPT has been regarded as the first protective barrier to prevent from peri‐implant disease progression (Hultin et al, ; Monje et al, ). A recent review further supports the importance of SPT after treatment of peri‐implantitis (Roccuzzo et al, ). In accordance with the findings, the statistical analysis in present review revealed that SPT patients obtained higher SR and lower prevalence of peri‐implant mucositis and peri‐implantitis during long‐term follow‐up.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…SPT has been regarded as the first protective barrier to prevent from peri‐implant disease progression (Hultin et al, ; Monje et al, ). A recent review further supports the importance of SPT after treatment of peri‐implantitis (Roccuzzo et al, ). In accordance with the findings, the statistical analysis in present review revealed that SPT patients obtained higher SR and lower prevalence of peri‐implant mucositis and peri‐implantitis during long‐term follow‐up.…”
Section: Discussionmentioning
confidence: 79%
“…SPT plays a critical role in maintaining the stability of periodontal status from the perspective of bacteria amount, clinical outcomes, and further disease progression (Lang & Tonetti, ; Ramfjord, ). Nevertheless, the concept of preventive maintenance should also be advocated in dental implants in terms of bacterial patterns (Agerbaek, Lang, & Persson, ; Ziebolz, Schmalz, Gollasch, Eickholz, & Rinke, ), cost‐effectiveness (Schwendicke, Tu, & Stolpe, ), biological complications (Berglundh et al, ; Salvi & Zitzmann, ), peri‐implant tissue and SR (Goh & Lim, ), and the long‐term stability of treated peri‐implantitis (Roccuzzo, Layton, Roccuzzo, & Heitz‐Mayfield, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recontouring of the bony architecture and smoothing of the implant surface may improve infection control. Regenerative procedures using a membrane and bone graft substitutes attempting to partially fill the bony defects caused by peri-implantitis can be successful [14]. Therapy of peri-implantitis followed by regular supportive care resulted in favorable clinical improvements and stable peri-implant bone levels in the majority of patients according to a systematic review [15].…”
Section: Introductionmentioning
confidence: 99%
“…A B Nevertheless, the perception among clinicians is that the peri-implantitis treatment is unpredictable and may not lead to success. 8 Esposito et al 9 in a systematic review on the therapy found that in some studies with a follow-up longer than 1 year, recurrence of peri-implantitis was up to 100% of the treated cases. In contrast, Renvert and coworkers found that stable clinical results could be achieved up to 5 years after initial therapy but highlighting that adequate oral hygiene across this period appeared to be an essential prerequisite.…”
Section: Resultsmentioning
confidence: 99%